Assessment of dental caries and salivary characteristics among type 1 diabetic Saudi children - Sami Abdoh Assiri; Omar Abd El Sadek El Meligy; Ibtesam Omar Alzain; Nada Othman Bamashmous (Elsevier, 2022)
Background/purpose: Type 1 diabetes mellitus (DM1) is considered the most common chronic disease in childhood. This study aimed to assess dental caries and salivary characteristics among a group of Saudi children with DM1. Materials and methods: Forty children with DM1 and 40 age- and gender-matched healthy controls were enrolled. A saliva sample was obtained to measure flow rate of saliva, buffering capacity, potential of hydrogen (pH), and bacterial counts. Oral examination and dental caries were recorded using Decayed, Missing, and Filled Teeth (dmft/DMFT) indices for primary/permanent teeth. Results: Children with DM1 showed higher DMFT scores with a mean of 3.5 compared to 2.8 in healthy children. The differences between both groups were not statistically significant (P = 0.14). Regarding dmft score, children with DM1 showed a significantly lower mean score of 4.5 compared to 6.5 in healthy children (P = 0.019). The flow rate of saliva showed a non-significant reduction in children with DM1 compared to healthy children with a mean of 0.86 and 0.96, respectively (P = 0.24). The mean salivary pH was found to be higher in the healthy group, but this was statistically non-significant (P = 0.118). The buffering capacity was significantly lower in children with DM1 compared to healthy children (P = 0.013). Mutans streptococci (MS) and Lactobacilli counts were found to be not significantly different between both groups (P = 0.422, P = 0.118 respectively). Conclusion: Children with DM1 showed remarkably lower caries experience in primary teeth and lower buffering capacity compared to healthy children.